Exploring transmedia storytelling as an approach to assessment in problem-based learning - Berezina, E * (2020)
In this paper, we discuss the recently developed edutainment approach – transmedia storytelling – as a tool for assessment of subjects that adopt the Problem-Based learning approach. Transmedia storytelling was used as a part of the assessment strategy for the third-year elective subject for psychology students in a private University in Malaysia. 85 third-year students had been implementing projects to promote mental health using a variety of social media within 12 weeks. The results show that transmedia storytelling could be incorporated as part of the assessments in higher education as it fulfils academic expectations, maintains student motivation and creates an interactive platform for communication between educators, students and the general public.